2014
DOI: 10.3329/bjp.v9i1.17474
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis of curcumin analogues as human neutrophil elastase inhibitors

Abstract: In the present study, we aimed to dock 17 different ligands of curcumin analogues with that of human neutrophil elastase. Molecular descriptors analysis using Molinspiration online tool was carried out including investigation on human neutrophil elastase putative binding sites using Discovery Studio. The molecular physicochemical analysis revealed that all of the curcumin analogues complied well with the five rules of thumb. With regard to bioactivity score, compound 17 has exhibited least score towards nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…In the present study, both ligands showed interaction with Ser195 amino acid residue of HNE; this was good in agreement with previous reports. [ 23 24 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, both ligands showed interaction with Ser195 amino acid residue of HNE; this was good in agreement with previous reports. [ 23 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are a group of zinc-dependent endopeptidase which is capable of degrading ECM components, and among the MMPs family, MMP-2 and -9 were reported to be elevated in the pathological conditions such as inflammation, wound healing, cancer, and aging. [ 24 ] The docking studies and binding free energy reported in Table 9 show that 4-hydroxyisoleucine had the highest interaction energy (−43.47 kcal/mol) with that of MMP-2, but phytic acid fails to dock with the MMP-2. 4-hydroxyisoleucine showed interaction with Ala165, His201, and Glu202 amino acid residues of MMP-2 as shown in Table 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction is an important tool for compound selection and prioritization in rational drug design. The information helps reduce the time and computational cost of screening compound libraries to select compounds feasible for synthesis and further testing [ 23 , 24 ]. The results are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Molecular properties of the ligands docked were calculated by Molinspiration server and the likeliness of drug was checked by Lipinski's Rule of Five. An ideal drug molecule should be having a molecular weight of less than 500, total number of hydrogen bond should not exceed 5, miLogP value and should be less than 5 and the sum of N and O should not be more than 10, (Narayanaswamy 2013).…”
Section: Methodsmentioning
confidence: 99%